Mengamati Perkembangan Anak Usia 10 Tahun yang menggalami gangguan cerebral palsy (kelumpuhan otak) Melalui Observasi Kunjungan Ke Rumah - Ramadhan Lubis; Zhafira nur’ulya Alsa; Alfiani Maulida; Aisyah Alya; Maaulida Afriani Nasution; Abrar Azizi (Jurnal Pendidikan Sosial Dan Konseling, 2025)
This study aims to describe the development of children aged 9–10 years, specifically fourth and fifth grade elementary school students, through home visit observations. A descriptive qualitative method was used, with data collected through interviews, direct observation, and documentation during the home visits. The focus of the observation includes cognitive, social-emotional, and self-reliance aspects of child development within the family environment. The results show that most children are in the concrete operational stage, in line with Piaget's theory, and are beginning to develop logical thinking skills. Socially, the children are showing emerging empathy, although they still require guidance in managing emotions. Family environment, parenting style, and interaction with family members significantly influence their development. These findings highlight the importance of collaboration between teachers, counselors, and parents in supporting optimal child development. Child development encompasses social, emotional, and intellectual aspects that are interrelated and play a vital role in shaping individual character and adaptive abilities. For a 10-year-old child with cerebral palsy (CP), these developmental processes face complex challenges due to central nervous system impairments that affect motor functions and are often accompanied by cognitive and emotional disturbances. The aim of this paper is to examine the dynamics of social, emotional, and intellectual development in 10-year-old children with CP. The findings indicate that physical limitations and communication barriers hinder social interactions, increasing the risk of social isolation and rejection. Emotionally, children with CP are more vulnerable to anxiety, stress, and low self-esteem. Intellectually, children show varied abilities, with some being able to follow regular education, while others require specialized approaches based on the extent of their neurological impairment. Therefore, multidisciplinary interventions, family support, and inclusive learning environments are essential in optimizing the developmental potential of children with CP.